Current Situation of Vanadium Resources and New Process Progress of Vanadium Extraction from the Stone Coal Vanadium Ore - Jinwei QU; Na MA; Yuefang HU; Xiaoying WENG; Zhihe DOU (Kuangchan zonghe liyong, 2025)
The main occurrence minerals of vanadium include vanadium titanomagnetite, stone coal vanadium and vanadium lead ores. At present, the vanadium extraction processes of stone coal vanadium ore are mainly sodium roasting-water leaching and calcification roasting-acid leaching. The vanadium extraction rate of sodium roasting-water leaching process is low, and a large number of toxic and harmful gases are produced in the roasting process, which pollutes the environment. Although no waste gas is produced in the process of calcification roasting-acid leaching, there are many impurities in the acid leaching solution, which affects the quality of vanadium products. Based on the necessity of extracting vanadium from the stone coal vanadium ore, the latest technologies of extracting vanadium from stone coal vanadium ore are introduced, such as manganese dioxide oxidation leaching of stone coal vanadium ore, roasting leaching and comprehensive utilization of the stone coal vanadium ore, extraction of vanadium from the stone coal vanadium ore by sulfuric acid low temperature curing and column leaching, enhanced leaching of the stone coal vanadium ore by additive, new technology of vanadium extraction from stone coal vanadium ore by clean roasting. The advantages and disadvantages of the new process are discussed, and some suggestions for extracting vanadium from the stone coal vanadium ore are put forward to.